Amplatzer Plug to Occlude the Internal Iliac Artery During Endovascular Aortic Aneurysm Repair: A Large Multicenter Study. Issue 5 (May 2016) - Warein, E.; Feugier, P.; Chaufour, X.; Molin, V.; Malikov, S.; Bartoli, M.A.; Coscas, R.; Picquet, J.; Peyrot, H.; Favre, J.-P.; Steinmetz, E.; Ben Ahmed, S.; et al.
Abstract : Objective: During endovascular repair of abdominal aortic aneurysms (EVAR), in the absence of a distal iliac landing zone, the Amplatzer plug is increasingly being used to replace other internal iliac artery (IIA) embolization techniques. This study aimed at assessing the technical success, complication occurrence, and durability of the Amplatzer plug for IIA embolization. Method: From January 1, 2007 to December 31, 2013, all consecutive patients who underwent internal iliac embolization with an Amplatzer plug during EVAR were included in the study. There were 169 patients, (160 men, 9 women, mean 75 ± 9 years), treated by unilateral (158 cases, 93%) or bilateral (11 cases, 7%) embolization of the IIA, performed either separately prior to (65 cases, 38.5%) or during EVAR (104 cases, 61.5%). Follow up CT scan and/or US scan were performed 1 month after treatment and yearly thereafter. The inclusions were done retrospectively but the series was continuous and consecutive. Data were collected and analyzed using acquisition REDCap software. Results: The technical success rate was 97.6%. Failures were device migration ( n = 1), navigation failure ( n = 2), and release outside the target zone ( n = 1). On average, 1.43 plugs were required to achieve the embolization. The average amount of contrast agent for the embolization procedure was 111 ± 51 mL and the radiation dose was 127, 777 ± 89, 528 mGy/cm 2 . The total fluoroscopy time was 854 ± 538 seconds. No re-canalization of the IIA trunk was observed during follow up. Complications were buttock claudication ( n = 41, 24.3%), which resolved in 24 cases (58.5%, 24/41) at the first follow up, and intestinal ischemia requiring limited bowel resection in two cases. Conclusion: This multicenter study is the largest published to date. It demonstrates the efficacy and reliability of the Amplatzer plug to embolize the IIA during EVAR, with few side effects.